Business Ethics in Online Transactions: A Study of Sellers’ Perceptions and Practices on Local E-Commerce Platforms in Padang - Muhammad Dio Rizki; Dian Oldisan; Seven Putra; Yull Hartono; Mukti Diapepin (Westscience Press, 2026)
Online transactions provide major opportunities for local sellers to expand their markets, but also create ethical issues related to the honesty of product information, photo suitability, pricing, service, complaint handling, shipping responsibility, and buyer data protection. This study aims to analyze seller perceptions and practices of business ethics on local e-commerce platforms in Padang City. This study used a descriptive qualitative approach through semi-structured interviews with online sellers who actively market products online. Data were analyzed using thematic coding through data reduction, code grouping, theme development, and interpretive meaning-making. The results show that sellers understand business ethics as honesty, responsibility, good service, and the ability to maintain buyer trust. Ethical business practices are reflected in clear product information, suitable product photos, non-misleading promotions, polite communication responses, complaint resolution through product exchange or refund, receipt tracking assistance, and protection of buyers’ personal data. The main obstacles to implementing business ethics include price competition, increasing capital costs, impatient buyers, and delivery delays. The findings confirm that business ethics serves as reputational capital for online sellers because it can increase trust, repeat orders, and long-term relationships with customers.